Enhancement of the Magnetoresistance in the Mobility‐Engineered Compensated Metal Pt5P2. (29th December 2022) - Mayo, Alex H.; Takahashi, Hidefumi; Ishiwata, Shintaro; Górnicka, Karolina; Winiarski, Michał J.; Jaroszynski, Jan; Cava, Robert J.; Xie, Weiwei; Klimczuk, Tomasz
Abstract: The magnetoresistance (MR) in nonmagnetic materials continues to be a fertile research area in materials science. The search for giant, positive MR has been limited to a rather small window of materials such as high‐mobility semimetals in single‐crystalline form. Here, the observation of a very large positive MR in metallic Pt5 P2 in polycrystalline form is reported. The observations reveal that improvement of the crystallinity results in a significant enhancement of the positive MR, exceeding 10 000% at 9 T, comparable to high‐mobility semimetals. Based on first‐principles calculations combined with magnetotransport and thermoelectric measurements, the Fermi surface of Pt5 P2 is found to consist of a collection of multiple electron and hole pockets compensating one another, along with a characteristic pocket continuously connected to the adjacent Brillouin zone, together with possible topologically protected band crossings. This work extends the landscape of high MR candidate materials to polycrystalline metals, which demonstrates the importance of crystallinity and purity of the samples for the optimization of the MR. Abstract : The search for giant, positive magnetoresistance (MR) is limited to a small window of materials such as high‐mobility semimetals in single‐crystalline form. The observation of a very large positive MR in metallic Pt5 P2 in polycrystalline form is reported. The observations reveal that improvement of the crystallinity results in a significant enhancement of the positive MR, exceeding 10 000% at 9 T.